Incidence of vascular and biliary anomalies found during laparoscopic cholecystectomy and their outcomes - Shaik, Kalesha; Babu, Bathula Aravind (International Journal Of Community Medicine And Public Health, 2025)
Background: Laparoscopic cholecystectomy represents the preferred surgical approach for gallbladder pathology, yet remains technically challenging due to frequent anatomical variations of the hepatobiliary system. Undetected preoperatively in many cases, these anomalies substantially influence procedural difficulty and patient outcomes. This investigation systematically evaluated their incidence and clinical consequences. Methods: This was a prospective observational study conducted at a tertiary care center from April 2023 to April 2024, enrolling 50 consecutive patients meeting inclusion criteria. Intraoperative documentation of vascular and biliary variations was performed, with subsequent analysis of operative duration, complication rates, and conversion frequencies. Statistical comparisons employed appropriate tests with significance set at p<0.05. Results: Among study participants, 26% demonstrated anatomical variations- predominantly biliary (20%) rather than vascular (6%). Specific anomalies included short cystic duct (6%), accessory bile ducts (10%), and double cystic artery (2%). Procedures involving anatomical variations required significantly extended operative times (p=0.047), with 23% exceeding two hours compared to 5% in standard anatomy cases. The overall complication rate remained low (8%), including bile leaks (4%) and hemorrhage (2%), without statistically significant difference between groups (p=0.72). Conversion to open procedure occurred in 6% of cases, principally due to challenging dissection (4%) or significant bleeding (2%). Conclusions: While anatomical variations prolong operative duration during laparoscopic cholecystectomy, meticulous surgical technique maintains acceptable complication rates. These findings underscore the importance of preoperative imaging evaluation and intraoperative vigilance. Future technological advances in three-dimensional reconstruction and robotic assistance may further enhance procedural safety in complex anatomical scenarios.